Some Aspects of Laplace Autoregressive Model on Application Point of View: A Review of Laplace Autoregressive Model for Time Series Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nowadays time series models are major tools for data analysis and forecasting the various real life situations. The forecasting of time series data provides useful information to the organization which is necessary for making important decisions for government organizations as well as private organizations. The Laplace Autoregressive model is not a very new concept but a few practical, real life work has till be done up to present date. In this paper, we are providing a review on Laplace autoregressive time series model. We discussed the overall Laplace autoregressive model with various modifications for analysis of various time series data. This study gives the reader an informed about the various researches that take place within Laplace autoregressive model approach using the time series analysis.